System Productivity of Potato + Maize Intercropping as Affected by Sowing Date - Begum, AA; Bhuiya, MSU; Hossain, SMA; Khatun, Amina; Das, SK; Sarker, MY (Bangladesh Agronomy Journal, 2017)
The experiment was conducted at Agronomy Research Field, Bangladesh Agricultural Research Institute (BARI), Gazipur during 2009-2010 to find out suitable sowing time of maize in potato + maize intercropping for maximum yield and economic return. Treatments of the experiment were: T1= Simultaneous sowing (SS) of potato and hybrid maize (HM), T2= SS of potato and composite maize (CM), T3= HM sown 10 days after potato planting (DAPP), T4= CM sown 10 DAPP, T5= HM sown 20 DAPP, T6= CM sown 20 DAPP, T7= HM sown 30 DAPP, T8= CM sown 30 DAPP, T9= HM sown 40 DAPP, T10 = CM sown 40 DAPP, T11= Sole potato, T12= Sole HM and T13= Sole CM. The result revealed that sole potato and maize produced the highest yield, LAI, TDM and CGR. The HM showed better performance than CM. The highest equivalent yield a monetary return indicated that potato + HM sown 30 DAPP intercropping was the most productive and profitable. Bangladesh Agron. J. 2016 19(2): 11-20